Calcium-Mediated Abiotic Stress Signaling in Roots - Wilkins, Katie A.; Matthus, Elsa; Swarbreck, Stéphanie M.; Davies, Julia M. (Frontiers in Plant Science, 2016)
Roots are subjected to a range of abiotic stresses as they forage for water and nutrients. Cytosolic free calcium is a common second messenger in the signalling of abiotic stress. In addition, roots take up calcium both as a nutrient and to stimulate exocytosis in growth. For calcium to fulfil its multiple roles must require strict spatio-temporal regulation of its uptake and efflux across the plasma membrane, its buffering in the cytosol and its sequestration or release from internal stores. This prompts the question of how specificity of signaling output can be achieved against the background of calcium’s other uses. Threats to agriculture such as salinity, water availability and hypoxia are signalled through calcium. Nutrient deficiency is also emerging as a stress that is signaled through cytosolic free calcium, with progress in potassium, nitrate and boron deficiency signaling now being made. Heavy metals have the capacity to trigger or modulate root calcium signaling depending on their dose and their capacity to catalyse production of hydroxyl radicals. Mechanical stress and cold stress can both trigger an increase in root cytosolic free calcium, with the possibility of membrane deformation playing a part in initiating the calcium signal. This review addresses progress in identifying the calcium transporting proteins (particularly channels such as annexins and cyclic nucleotide-gated channels) that effect stress-induced calcium increases in roots and explores links to reactive oxygen species, lipid signalling, and the unfolded protein response.